Secondary Education Systems and the General Skills of Less- and Intermediate-educated Adults: A Comparison of 18 Countries. (July 2015) - Heisig, Jan Paul; Solga, Heike
We investigate the impact of external differentiation and vocational orientation of (lower and upper) secondary education on country variation in the mean numeracy skills of, and skills gaps between, adults with low and intermediate formal qualifications. We use data on 30- to 44-year-olds in 18 countries from the 2011–12 round of the Program for the International Assessment of Adult Competencies. We find that higher levels of external differentiation (tracking) amplify skills gaps between less- and intermediate-educated adults. This is mainly due to lower mean skills achievement of less-educated adults. By contrast, greater emphasis on vocational skills in upper-secondary education is positively related to numeracy skills for both less- and intermediate-educated adults. Gains are larger for the less educated, so the gap in numeracy skills tends to fall with the degree of vocational orientation. We discuss implications of our findings for research on educational and labor market inequalities.